2018
DOI: 10.1007/s10552-018-1072-6
|View full text |Cite
|
Sign up to set email alerts
|

Review of non-clinical risk models to aid prevention of breast cancer

Abstract: A disease risk model is a statistical method which assesses the probability that an individual will develop one or more diseases within a stated period of time. Such models take into account the presence or absence of specific epidemiological risk factors associated with the disease and thereby potentially identify individuals at higher risk. Such models are currently used clinically to identify people at higher risk, including identifying women who are at increased risk of developing breast cancer. Many genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 96 publications
1
22
0
Order By: Relevance
“…The discriminative performance of these 12 models is generally high and comparable with other melanoma and cancer risk‐prediction models, where AUC ranges were 0·73–0·93 for melanoma, 11 0·56–0·89 for breast cancer, 12 0·63–0·70 for colorectal cancer 13 and 0·61–0·81 for lung cancer; 14 some of these models included age as a predictor. Similar to external validation studies of other cancer types, there is lower discrimination on external validation than on internal validation 13,14 .…”
Section: Published Risk Prediction Model (Country) Reported Auc (95% Ci) Unweighted Auc (95% Ci) On External Validation Weighted Auc (95%mentioning
confidence: 67%
“…The discriminative performance of these 12 models is generally high and comparable with other melanoma and cancer risk‐prediction models, where AUC ranges were 0·73–0·93 for melanoma, 11 0·56–0·89 for breast cancer, 12 0·63–0·70 for colorectal cancer 13 and 0·61–0·81 for lung cancer; 14 some of these models included age as a predictor. Similar to external validation studies of other cancer types, there is lower discrimination on external validation than on internal validation 13,14 .…”
Section: Published Risk Prediction Model (Country) Reported Auc (95% Ci) Unweighted Auc (95% Ci) On External Validation Weighted Auc (95%mentioning
confidence: 67%
“…In the past two decades, several breast cancer risk prediction models have been developed to evaluate a woman’s potential risk for this disease. In addition to the National Cancer Institute (NCI)’s summary on risk assessment models on breast cancer [13], three other systematic reviews have been done on this topic [1416]. Lee et al conducted a systematic review and identified 13 risk factors that were consistent throughout models [15].…”
Section: Review Of Existing Cancer Risk Prediction and Assessment Toomentioning
confidence: 99%
“…how predicted probabilities agree with observed proportions) but have less ability to discriminate (i.e. the ability to separate individuals into different classes) [14].…”
Section: Review Of Existing Cancer Risk Prediction and Assessment Toomentioning
confidence: 99%
“…Breast cancer remains the most frequently diagnosed malignancy and leading cause of cancer-associated deaths among females worldwide [1,2]. Despite significant declines in mortality, the incidence of breast cancer has risen more than 30% in the last 25 years [3,4]. Sex, genetic factors, use of hormone therapy, lifestyle and dietary habits, and age are the main risk factors for breast cancer [5].…”
Section: Introductionmentioning
confidence: 99%